When do we become adults? : Review of theory, research and recent advances from an interdisciplinary perspective - Knežević, Martina, psihologinja (Array, 2018)
Major developmental psychology theories, such as psychoanalytic, behavioural or cognitive, have tried to explain how people grow and change over the course of a lifetime. These theories have mainly focused on the stages of development early in life - from infancy to adolescence - leaving the impression that after adolescence no significant leaps in development occur. However, a large body of evidence that has emerged recently revealed that becoming an adult is much more complicated and temporally extended than previously believed. The aim of this paper was to use an interdisciplinary approach to tap into the issue of transition to adulthood by integrating recent brain and cognitive maturational findings from neuroscience and cognitive psychology while considering traditional and legal markers of adulthood. We first discuss some of the questions related to definitions of the period of adulthood through societal and legal frameworks. Next, we examine some of the prevailing views on protracted structural and functional brain maturation and its impact on cognitive development, emphasizing the need and the potential value of investigating how these changes may influence important life choices during early young adulthood that have long-lasting consequences. Finally, based on evidence from existing research, we highlight the importance of deeper appreciation and integration of findings from different research disciplines in order to better understand strengths and vulnerabilities of young adults.